Size dependence of uniformed carbon spheres in promoting graphitic carbon nitride toward enhanced photocatalysis - Liu, S.; Ke, J.; Sun, Hongqi; Liu, Jian; Tade, Moses; Wang, Shaobin (Elsevier BV, 2017)
Recently, graphitic carbon nitride (GCN) has been extensively employed as a metal-free, visible-light-responsive photocatalyst. The strong recombination rate of photo-induced charges and small surface area limit its wide applications. In this study, monodisperse carbon nanospheres (CS) with a uniform size were synthesized from resorcinol-formaldehyde resin using different surfactants and then loaded onto GCN via a hydrothermal treatment. It was found that the size of CS influenced the properties and photocatalytic performances of the CS/GCN hybrids. All the CS/GCN catalysts exhibited higher photocatalytic activities in degradation of water contaminants, antibiotic sulfachloropyridazine and methylene blue, under visible light irradiations. Photoluminescence spectra and photocurrent analysis indicated that hybridization with the carbon spheres at 200–500 nm will significantly reduce the electrocarrier recombination of carbon nitride while increase the photocurrent intensity, resulting in much better photocatalysis.